A network topology method for cluster communication based on wolf pack algorithm - LI Xuesi; WU Zheping; SHI Haobin; JI Qingbing (Xibei Gongye Daxue Xuebao)
The foundation of collaborative control of UAVs is to have a stable and reliable network communication environment, which depends on a high real-time and practical network topology method. This paper proposes a self-organizing topology method for cluster network communication based on wolf pack algorithm (NTM-WPA). Firstly, taking into account constraints such as the location of the UAVs and the load operation state of the UAVs, a multi constraint fusion equivalent distance is proposed. Secondly, the improved wolf pack algorithm is utilized to dynamically search for the shortest network communication path in the equivalent bidirectional communication connection diagram. Finally, the simulation analysis and experiment are designed and conducted, the results demonstrated that the proposed method has better real-time performance and practicality.